A review of decellularized stem cell matrix: a novel cell expansion system for cartilage tissue engineering - M Pei; JT Li; M Shoukry; Y Zhang (European Cells & Materials, 2011)
Cell-based therapy is a promising biological approach for the treatment of cartilage defects. Due to the small size of autologous cartilage samples available for cell transplantation in patients, cells need to be expanded to yield a sufficient cell number for cartilage repair. However, chondrocytes and adult stem cells tend to become replicatively senescent once they are expanded on conventional plastic flasks. Many studies demonstrate that the loss of cell properties is concomitant with the decreased cell proliferation capacity. This is a significant challenge for cartilage tissue engineering and regeneration. Despite much progress having been made in cell expansion, there are still concerns over expanded cell size and quality for cell transplantation applications. Recently, in vivo investigations in stem cell niches have suggested the importance of developing an in vitro stem cell microenvironment for cell expansion and tissue-specific differentiation. Our and other investigators’ work indicates that a decellularized stem cell matrix (DSCM) may provide such an expansion system to yield large-quantity and high-quality cells for cartilage tissue engineering and regeneration. This review briefly introduces key parameters in an in vivo stem cell niche and focuses on our recent work on DSCM for its rejuvenating or reprograming effect on various adult stem cells and chondrocytes. Since research in DSCM is still in its infancy, we are only able to discuss some potential mechanisms of DSCM on cell proliferation and chondrogenic potential. Further investigations of the underlying mechanism and in vivo regeneration capacity will allow this approach to be used in clinics.